Aplikasi Pemesanan Menu Makanan dan Minuman pada K&Y Coffee berbasis Android - Farid Asfaroni; Rahayu Amalia (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
This study aims to create an application for ordering food and beverage menus on Android-based K&Y Coffee. Currently, K&Y Coffee is still using a simple manual method in the menu ordering process. Where the cafe and customers still use pen and paper as a medium for ordering. This method is still not efficient, where customers are still waiting and queuing for the ordering process and cafe owners are still having trouble monitoring orders, managing menus and viewing sales reports. Therefore, the use of information technology will be very helpful in the ordering process. In this study, the method used is the selection of data types, namely primary data obtained from observations, literature studies and interviews. While the method used in the construction of this system is the Extreme Programming method. The implementation of this research uses Android Studio with Java, Kotlin, PHP (Hypertext Preprocessor) programming languages. The databases used are My SQL (My Structured Query Language) and UML (Unified Modeling Language) as a tool for system design and testing of this system using BlackBoxTesting. The results of this study are a system that will make it easier for cafe owners to manage menus and view sales reports and make it easier for employees and customers in the menu ordering process.